2007
DOI: 10.1108/09590550710828209
|View full text |Cite
|
Sign up to set email alerts
|

Consumer adoption of online music services

Abstract: Major UK music companies have struggled to formulate a coherent strategy to deal with the threat of illegal downloading and distribution of music files over the Internet.A variety of technical and political issues blocked inter-label cooperation initially, and those services that did go live were subsequently plagued by complaints of limited catalogues, unfriendly software and complicated license restrictions. It seemed to provide justification for consumers' free download and file-swapping behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 41 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, we have developed two new independent variables, the discovery of new content and social connectivity, that are highly relevant for a wide range of digital content services. As a result, this study adds to the prior literature on people's motives for consuming hedonic digital content online (Bhattacharjee, Gopal, Lertwachara, & Marsden, 2006;Kunze & Mai, 2007;Molteni & Ordanini, 2003;Sanchez-Franco & Rondan-Cataluña, 2010;Sjöblom & Hamari, 2017).…”
Section: Not Supportedmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, we have developed two new independent variables, the discovery of new content and social connectivity, that are highly relevant for a wide range of digital content services. As a result, this study adds to the prior literature on people's motives for consuming hedonic digital content online (Bhattacharjee, Gopal, Lertwachara, & Marsden, 2006;Kunze & Mai, 2007;Molteni & Ordanini, 2003;Sanchez-Franco & Rondan-Cataluña, 2010;Sjöblom & Hamari, 2017).…”
Section: Not Supportedmentioning
confidence: 80%
“…Freemium consumer behavior literature (Koch & Benlian, 2017;Wagner et al, 2014) Consumer value in digital content services (Bhattacharjee et al, 2006, Kunze & Mai, 2007, Molteni & Ordanini, 2003, Sanchez-Franco & Rondan-Cataluña, 2010, Sjöblom & Hamari, 2017.…”
Section: Source Of Contribution Description Area Of Contributionmentioning
confidence: 99%
“…Internet provides a lot of information on the products and services offered, and a variety of web sites where the web user can carry out transactions. Despite the fact that internet lowers the cost of acquiring information, consumers also incur time costs from using online portals, the time of learning how to buy on a certain e-retailing web site, the time to wait for it to respond and the additional cognitive effort expended in this expanded search process (Kunze and Li-Wei, 2007;Littler and Melanthiou, 2006). Moreover, in the case of internet shopping the time risk may be related to the time involved in dealing with erroneous transactions.…”
mentioning
confidence: 99%
“…Further, Flavián and Guinalíu (2006a, b) propose security risk as the technical aspect of ensuring the integrity, confidentiality, authentication and non-recognition of relationships. Researchers have found that security is a key dimension in studying user attitude toward online services (Kunze and Li-Wei, 2007;Polatoglu and Ekin, 2001;Suh and Han, 2002). Consumers associate security risk with loss of money (in cash or through the credit card).…”
mentioning
confidence: 99%
“…On the other hand, Stone and Grønhaug (1993) found that financial and psychological risks were the significant predictors of overall perceived risk in purchasing a personal computer. Kunze and Mai (2007) found that when consumers used an online music service, performance risk and time risk were the best predictors of overall perceived risk, whereas social risk and psychological risk were the poorest predictors.…”
Section: Perceived Riskmentioning
confidence: 97%